Radium Isotopes Across the Arctic Ocean Show Time Scales of Water Mass Ventilation and Increasing Shelf Inputs. Issue 7 (13th July 2018) - Rutgers van der Loeff, Michiel; Kipp, Lauren; Charette, Matthew A.; Moore, Willard S.; Black, Erin; Stimac, Ingrid; Charkin, Alexander; Bauch, Dorothea; Valk, Ole; Karcher, Michael; Krumpen, Thomas; Casacuberta, Núria; et al.
Abstract: The first full transarctic section of 228 Ra in surface waters measured during GEOTRACES cruises PS94 and HLY1502 (2015) shows a consistent distribution with maximum activities in the transpolar drift. Activities in the central Arctic have increased from 2007 through 2011 to 2015. The increased 228 Ra input is attributed to stronger wave action on shelves resulting from a longer ice‐free season. A concomitant decrease in the 228 Th/ 228 Ra ratio likely results from more rapid transit of surface waters depleted in 228 Th by scavenging over the shelf. The 228 Ra activities observed in intermediate waters (<1, 500 m) in the Amundsen Basin are explained by ventilation with shelf water on a time scale of about 15–18 years, in good agreement with estimates based on SF6 and 129 I/ 236 U. The 228 Th excess below the mixed layer up to 1, 500 m depth can complement 234 Th and 210 Po as tracers of export production, after correction for the inherent excess resulting from the similarity of 228 Ra and 228 Th decay times. We show with a Th/Ra profile model that the 228 Th/ 228 Ra ratio below 1, 500 m is inappropriate for this purpose because it is a delicate balance between horizontal supply of 228 Ra and vertical flux of particulate 228 Th. The accumulation of 226 Ra in the deep Makarov Basin is not associated with an accumulation of Ba and can therefore be attributed to supply from decay of 230 Th in the bottom sediment. We estimate a ventilation time of 480 years for the deep Makarov‐Canada Basin, in good agreement with previous estimates using other tracers. Key Points: The increase of 228 Ra in central Arctic surface waters points at stronger sediment water exchange due to the longer ice‐free season on Arctic shelves The decrease in 228 Th/ 228 Ra in the Transpolar Drift may be related to the increase in the rate of the drift Excess 228 Th in intermediate depths (100–1, 500 m) may be used as tracer of export production